Evaluation of ultrasonic intravascular thrombectomy system on a rabbit model in the treatment of deep vein thrombosis - Kasimzade, Ferit; Ada, Fatih; Karataş, Özhan (Journal of Surgery and Medicine, 2021)
Background/Aim: Advanced treatment options are needed in deep venous thrombosis (DVT), which is a special subgroup of venous disease. We examined this subgroup on an animal model and aimed to evaluate the effects of the ultrasonic intravascular thrombectomy system on vascular endothelial damage. Methods: A total of 24 rabbits in 3 groups were used in the study. DVT was created in the common iliac vein by the administration of intravascular fibrin. One hour passed for DVT formation. The ultrasonic intravascular thrombectomy system and the mechanical thrombectomy system were used separately in the DVT groups. After one hour, samples obtained from the groups were examined histologically. Results: Significantly less endothelial damage was detected in the ultrasonic intravascular thrombectomy system group compared to the mechanical thrombectomy group (P<0.05). Conclusions: Ultrasonic intravascular thrombectomy method minimizes the thrombus load and causes minimal endothelial damage. These findings show that the ultrasonic intravascular thrombectomy method can be used successfully in DVT treatment.